2022
DOI: 10.3389/fcvm.2022.882303
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Clinical Outcomes After Percutaneous Coronary Intervention With Drug-Coated Balloon-Only Strategy in de novo Lesions of Large Coronary Arteries

Abstract: Background and ObjectivesUse of drug-coated balloon (DCB)-only strategy for revascularization of native large coronary artery lesions is on the rise. The long-term efficacy of this approach for bifurcation and non-bifurcation lesions remains unknown. We aim to assess the long-term clinical outcomes of DCB-only strategy for the treatment of de novo bifurcation and non-bifurcation lesions in large coronary arteries.MethodsThis multicenter, prospective, observational study enrolled 119 patients with de novo coron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…Data on the long-term efficacy of DCB in large coronary vessels are scantbecause in most of the studies the follow up is lower than 1 year. A longer follow up (2 years) is available in the study of Hu et al 18 that evaluated the efficacy of a paclitaxelcoated DCB in de novo lesions ≥2.75 mm showing a TLR of 3.4%, similar to the one observed here in the cohort of de novo lesions.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Data on the long-term efficacy of DCB in large coronary vessels are scantbecause in most of the studies the follow up is lower than 1 year. A longer follow up (2 years) is available in the study of Hu et al 18 that evaluated the efficacy of a paclitaxelcoated DCB in de novo lesions ≥2.75 mm showing a TLR of 3.4%, similar to the one observed here in the cohort of de novo lesions.…”
Section: Discussionsupporting
confidence: 76%
“…Data on the long‐term efficacy of DCB in large coronary vessels are scantbecause in most of the studies the follow up is lower than 1 year. A longer follow up (2 years) is available in the study of Hu et al 18 that evaluated the efficacy of a paclitaxel‐coated DCB in de novo lesions ≥2.75 mm showing a TLR of 3.4%, similar to the one observed here in the cohort of de novo lesions. In our study too, the follow up was extended up 2 years demonstrating a TLR of 9% in the whole population but only a 4% rate in the de novo sub‐group, representing the largest registry with the longest follow up testing a sirolimus DCB in the treatment of large coronary vessel.…”
Section: Discussionsupporting
confidence: 75%
“…However, the safety and efficacy of DCB treatment beyond 3 years for de novo coronary lesions remain unestablished, and previous studies of de novo non-small coronary lesions have reported conflicting results limited by the absence of a control group treated with DES implantation. 11 21 22 …”
Section: Discussionmentioning
confidence: 99%
“…Recent observational studies have indicated that the efficacy and safety of DCB treatment are comparable for de novo non-small coronary lesions and small vessel disease. 10 11 Her, et al 10 demonstrated that target vessel failure (TVF) rates were similar between groups at 3.4 years of follow-up (large vessel group, 7.0% vs. small vessel group, 7.9%; p =0.596). Another recent meta-analysis indicated that DCB treatment was non-inferior to DES implantation for de novo large coronary lesions in terms of target lesion revascularization at 6–9 months of follow-up [risk ratio (RR):1.17; 95% CI: 0.46–2.95; p =0.746].…”
Section: Introductionmentioning
confidence: 98%
“…Pre-dilation is the most important factor that needs to be considered when treating coronary arteries[ 16 ]. To prevent the requirement of dissection during semi-compliant balloon dilation, the ratio of the balloon and vessel diameter should be between 0.8 and 1.0[ 17 ].…”
Section: Discussionmentioning
confidence: 99%